ANALISIS STRATEGI BISNIS DI SAAT PANDEMI COVID-19 PADA CAFE WANOWAN DI BANDAR LAMPUNG - Habiburrahman Habiburrahman; Felicia Felicia; Hepiana Patmarina (Jurnal Manajemen dan Bisnis, 2022)
The quantity of coffee store groups and coffee stores calls for techniques for coffee keep proprietors to compete with competitors. Further, the usage of the contemporary COVID-19, of course, impacts the internet cafe business without delay. Marketers truely need to rack their brains to keep their business. The unique motive of the survei itself is to find out what factors propose the success of Cafe Wanowan's techniques and the choice on the right business approach for Cafe Wanowan Bandar Lampung to enforce within the midst of COVID-19. Concerning the statistics series method, researchers used information collection techniques in the form of interviews, observations, questionnaires and documentation. The analytical method used within the survei is the gentle device method (SSM) approach with the experience of evaluation (AHP). The survei effects show that there are three sub-standards on inner and outside elements. because of making choices the usage of AHP, he said that the overriding approach became to apply a variety of interesting dishes and hold the flavor supplied, observed by means of participating with 0.33 events to convey exciting promotions and increase merchandising/marketing with social media to support them in retaining the Wanowan Cafe commercial enterprise inside the midst of a plague.